KAJIAN HUKUM TENTANG PERNIKAHAN DINI - Misbahul Amin, M.; Wahid, Abdurrohman (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2022)
To bridge the realization of marriage in accordance with the purpose of the marriage, the marriage law No. 1 of 1974 has determined and stipulates the basics that must be carried out in marriage. One of them is article 7 paragraph 1 which reads "Marriage is only permitted if the man has reached the age of 19 years and the woman has reached the age of 16 years" and in the next paragraph states that if there are deviations in article 7 paragraph (1) can ask for dispensation at the court or other official appointed by both parties, both male and female. Later article 7 of Law no. 1 of 1974 concerning the minimum age for marriage was revised by Law no. 16 of 2019 which states that marriage is only permitted if a man and a woman have reached the age of 19 (nineteen years). Early marriage has the potential to cause various impacts on family harmony, due to lack of physical and psychological preparation in forming a sakinah family. Although in fiqh there is no explicit minimum age for marriage, for the benefit of the state, this is necessary.